2018
DOI: 10.5603/arm.a2018.0046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Omalizumab Therapy on Airway Remodeling Assessed with High-Resolution Computed Tomography (HRCT) in Severe Allergic Asthma Patients

Abstract: Introduction: Airway remodeling is an important factor in persistent obstruction in severe asthma. High resolution computed tomography (HRCT) is an effective method of detecting changes in airway structure. Our aim was to use HRCT to assess changes in airway remodeling in patients with severe allergic asthma who are treated with omalizumab. Material and methods: In 12 patients with severe allergic asthma, HRCT was performed before and after treatment with omalizumab. In selected bronchial airways, parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Moreover, imaging examinations, especially CT, are also considered a useful way to assess airway remodeling in human asthma subjects. However, all of these techniques are limited by practicality and ethicality (28).…”
Section: Research Dilemmas In Airway Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, imaging examinations, especially CT, are also considered a useful way to assess airway remodeling in human asthma subjects. However, all of these techniques are limited by practicality and ethicality (28).…”
Section: Research Dilemmas In Airway Remodelingmentioning
confidence: 99%
“…A wealth of clinical trials regarding monoclonal antibodies suggested that a variety of IL-5 monoclonal antibodies (e.g., mepolizumab and reslizumab) can facilitate airway remodeling in asthma, including reducing the expression of ECM protein in the RBM, thereby partially restricting airway remodeling (48). For patients with long-term asthma with persistent airway obstruction, however, the current biologics have limited effects (28,(88)(89)(90). Though largescale clinical trials have suggested that the new monoclonal antibodies against IL-4/IL-13, [e.g., dupilumab and tralokinumab (91,92)] can effectively reduce the onset of asthma and improve FEV1, their exact effects on airway remodeling require further research.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Several studies have reported that bronchial wall thickness was improved by ICSs or omalizumab treatment in adult patients with severe asthma. 23 25 Airway wall thickness on CT images includes not only irreversible tissue structural changes, but also reversible airway mucosal changes caused by swelling or the infiltration of inflammatory cells. 26 This reversible mucous membrane thickness in the airways can be reduced by the initiation of an ICS or omalizumab to suppress airway inflammation, resulting in improved airway wall thickness in CT images.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies using biopsied bronchial tissue before and after omalizumab treatment in adult patients with severe asthma showed a significant reduction in bronchial reticular basement membrane thickness, airway smooth muscles, and fibronectin deposition [ 134 , 135 , 136 ]. Furthermore, three studies using CT airway analysis gave similar assessments, reporting that omalizumab treatment in adult patients with severe asthma significantly reduced airway wall thickness and area [ 137 , 138 , 139 ]. The improving effect on airway remodeling has been confirmed not only with omalizumab, but also with other biological drugs.…”
Section: Inhibitory Effect Of Airway Remodeling By Biological Drugsmentioning
confidence: 95%